Incremental value of cardiovascular magnetic resonance feature tracking derived atrial and ventricular strain parameters in a comprehensive approach for the diagnosis of acute myocarditis. Issue 104 (July 2018) - Doerner, Jonas; Bunck, Alexander C.; Michels, Guido; Maintz, David; Baeßler, Bettina
Highlights: FT derived atrial and ventricular strain showed good diagnostic performance in patients with myocarditis. Left atrial and right ventricular strain can be helpful in patients with myocarditis and preserved ejection fraction. Diagnostic performance can be enhanced when LLC are combined with strain parameters. Abstract: Purpose/introduction: This study aims to evaluate the incremental diagnostic value of cardiac magnetic resonance (CMR) feature tracking (FT) derived atrial and ventricular strain-analysis in patients with acute myocarditis (myocarditis) as an additional tool to established Lake-Louise criteria (LLC). Material and methods: A total of 86 patients with clinically proven myocarditis and 30 healthy controls underwent a comprehensive CMR protocol. In addition to established LLC, FT derived strain parameters from the left (LA) and right atrium (RA) as well as the left (LV) and right ventricle (RV) were assessed. Receiver operating characteristics analysis was performed to compare diagnostic performance. Results: Patients with myocarditis showed significantly reduced LA passive strain (LA εe : 26.3 ± 14.5 vs. 33.5 ± 10.1%, p = .007), LA peak early negative strain rate (LA SRe: −1.94 ± 0.59 1/s vs. −1.46 ± 0.62 1/s, p < .001), LV global longitudinal strain (LV GLS: −17.2 ± 4.9% vs. −13.3 ± 6.2%, p < .001), LV midventricular circumferential strain (LV mid CS: −25.9 ± 4.7% vs. −22.0 ± 6.5%, p < .001), and an increased RV basal circumferential SR (RV basal CSR: −0.70 ± 028 vs. −0.58 ± 0.34 1/s, p = .096) compared to healthy controls. In a subgroup analysis of patients with myocarditis and preserved LV function, RV basal CSR was also significantly increased compared to healthy controls (−0.74 ± 0.27 vs. −0.57 ± 0.26 1/s; p = .035) whereas LA SRe (−1.49 ± 0.59 vs. −1.32 ± 0.74%; p = .005) was significantly reduced. In multinominal logistic regression analysis, LA SRe and RV basal CSR proved to be the best independent predictors of myocarditis with preserved LV function. Combined with LLC, strain parameters enhanced the diagnostic performance in such patients (Areas under the curve (AUC): LLC: 0.78, LLC + LV GLS + LA SRe: 0.86), whereas LA SRe was the best performing single parameter (AUC: 0.72). Conclusion: Combining quantitative CMR derived atrial and ventricular strain parameters with established LLC parameters can improve the diagnostic performance in patients with suspected myocarditis, including those with preserved LV function. Further investigations should focus on LA function, which appears to be more sensitive to early functional changes than LV function.